An assessment of the level of emotional intelligence attributes of undergraduate built environment students in developing countries. Issue 2 (April 2019) - Owusu-Manu, D.; Edwards, D.J.; Kukah, A.S.; Pärn, E.A.; El-Gohary, H.; Aigbavboa, C.
Built environment students graduate with good technical skills but often lack the rudiments of management and leadership skills. Other challenges they face, among others, include interpersonal skills, emotional skills, self-awareness and impulse control. This article presents a case study assessing the emotional intelligence (EI) attributes of built environment students. EI questionnaires (Emotional Quotient Inventory (EQ-i)) were distributed to fourth-year undergraduates studying construction-related courses at Kwame Nkrumah University of Science and Technology in Ghana. A total of 182 questionnaires were completed and retrieved from the fourth-year students. Analytical tools included descriptive statistics, mean score ranking, regression and correlation. Construction technology management students had the highest EI value, followed by civil engineering students, quantity surveying and construction economics students and lastly architecture students. There was no significant difference in the overall EQ-i scores of the students. Furthermore, there is insignificant correlation between the built environment programmes and the EI level of the students. The results illustrate that the EI level of the students is not statistically dependent on the programmes undertaken. From regression analysis, age is a significant predictor of EI. This study presents a methodology for assessing the EI levels of built environment students in developing countries and adds to the body of knowledge. The work concludes with directions for future research.